THE THE HEPARIN INDUCED THROMBOCYTOPENIA IN CARDIAC SURGERY PATIENTS - Khadim, Shakila; Salamat, Nuzhat; Khan, Saleem Ahmad; ., Kifayatullah; ., Nisaruddin; Naeem, Muhammad Abdul (Pakistan Armed Forces Medical Journal, 2020)
Objective: Combination of ‘4Ts’ clinical scoring system and Particle gel immunoassay to determine the frequency of heparin-induced thrombocytopenia during heparin treatment in cardiac surgery patients.Study Design: Prospective observational study.Place and Duration of Study: This study was conducted in the Pathology Department, Army Medical College incollaboration with Armed Forced Institute of Cardiology and Armed Forced Institute of Transfusion, Rawalpindi,from Jan 2019 to Dec 2019.Methodology: A total of 115 suspected cases of heparin-induced thrombocytopenia irrespective of age and gender were included in the study. A clinical scoring system the ‘4Ts’ was used for the classification of patients based on probability into three groups such as low, intermediate, and high probability groups. For the detection of antibodies against heparin/platelet factor 4 complexes, the Particle gel immunoassay was used.Results: There were 39 (33.9%) females and 76 (66.1%) males, the age range of 20 to 86 ± 12.9 years. Among the low probability group, there was no positive result, 2 (2.3%) patients showed positive serological evidence in the intermediate probability group. In the high probability group, 4 (23.5%) patients showed positive results with the chosen assay.Conclusion: Heparin-induced thrombocytopenia was found an overall 5.2% of patients undergoing cardiacsurgery receiving unfractionated heparin. A combination of ‘4Ts’ pretest clinical scoring systems followed byPaGIA constitutes a simple strategy to screen for heparin-induced thrombocytopenia in suspected patients. This will avoid serious complications if the detection is not delayed.